LEVELING OF CRITICAL THINKING ABILITIES OF STUDENTS OF MATHEMATICS EDUCATION IN MATHEMATICAL PROBLEM SOLVING - Rasiman Rasiman (Journal on Mathematics Education, 2015)
This research aims to determine the leveling of critical thinking abilities of students of mathematics education in mathematical problem solving. It includes qualitative-explorative study that conducted at University of PGRI Semarang. The generated data in the form of information obtained problem solving question and interview guides. The results are: (1) students who are not critical (LCTA-0) only able to identify the given facts clearly, (2) students are less critical (LCTA-1), students can identify the facts in problems, (3) critical student (LCTA-2), students can identify the fact in problems, revealing the prerequisite knowledge appropriately, solve the problem but still less accurate in every stage, and (4) students are very critical (LCTA-3), students can identify the facts given clearly, mention the concept/ theorem/ prerequisite material. Based on these results, the leveling of students critical thinking abilities can be applied in a lecture at mathematics education.Keywords: leveling, critical thinking, mathematical problemÂ DOI: dx.doi.org/10.22342/jme.61.40